The Post Office, The Admiralty and Letters to Sailors in the Napoleonic Wars. Issue 2 (3rd April 2019) - Vale, Brian
Abstract : By 1790 the Post Office ran a service using mail coaches and sailing packets that was fast, safe and reliable. High postal rates, however, restricted its use to merchants and the more affluent, and there were no special arrangements for the armed services. In 1795 this changed. Recognizing the benefits to morale, the authorities introduced a scheme whereby soldiers and sailors could send and receive letters at a cost of only one penny. This generated an increase in letter writing by seamen who were delighted to receive news from home. The Admiralty left the scheme in the hands of the Post Office, which tried to deal with it using its normal processes. This article describes how mail got to, and was collected from sailors, and the problems which arose when ships were increasingly deployed outside home waters where their locations were unknown or frequently changed. It describes the difficulties and successes of the Post Office and its, at times, uneasy relationship with an Admiralty reluctant to give information on ship movements. As the wars progressed, British successes at sea removed many initials problems, and the scheme become so well established that it continued after 1815.